The Relationship Between Adolescents’ Locus of Control and Healthy Dietary Behaviours and its Implications for School Psychologists and Other Health Related Professionals - Piyal, Birgül; Tabak, Ruhi Selçuk; Çelen, Ümit; Karakoç, Şerife; Özen, Yelda (SAGE Publications, 2009)
The Concept of Health Locus of Control (HLOC) indicates the personal belief of an individual about who or what affects his/her health. This approach emphasizes the importance of individual responsibility for health, especially in the school years which represent a ‘critical period’ for students to adopt healthy behaviours and lifestyles. The main aim of this survey is to define relationships between Health Locus of Control and the dietary behaviours of Turkish adolescent students by evaluating their risky health behaviours. Results of this survey are used for prediction of how to modify positive health behaviours of students for the protection and promotion of their health. The study group of this descriptive study consists of primary and secondary school students (831) in Ankara. The results not only clearly indicate the relationship between HLOC and dietary behaviours of adolescent students, but also support the results of earlier research. In particular, the association between the relatively higher Chance-HLOC, which represents low responsibility for health, and risky dietary behaviours of students is striking. The Internal-HLOC of students has been found to be more effective than External-HLOC in maintaining healthy dietary behaviours. School psychologists and health educators need to emphasize HLOC in educational activities for reduction of risky behaviours.
Keywords: 2. Zero hunger; 5. Gender equality; 4. Education; 3. Good health